Transcranial Sonographic Alterations of Substantia Nigra and Third Ventricle in Parkinson's Disease with or without Dementia - Zhi-Fen Dong (Chinese Medical Journal, 2017)
Background: Numerous studies have demonstrated that patients with Parkinson's disease (PD) have a higher prevalence of substantia nigra (SN) hyperechogenicity compared with controls. Our aim was to explore the neuroimaging characteristics of transcranial sonography (TCS) of patients with PD and those with PD with dementia (PDD). The correlation between the echogenicity of the SN and clinical symptoms in Chinese patients with PDD was also assessed. Methods: The ratios of SN hyperechogenicity (SN+), maximum sizes of SN+, and widths of third ventricle (TV) were measured using TCS for all the recruited patients. Data were analyzed using one-way analysis of variance, rank-sum test, Chi-square test, and receiver-operating characteristic (ROC) curve analysis. Results: The final statistical analysis included 46 PDD patients, 52 PD patients, and 40 controls. There were no significant differences in ratios of SN+ and maximum sizes of SN+ between PDD and PD groups (P > 0.05). TV widths were significantly larger in PDD group (7.1 ± 1.9 mm) than in PD group (6.0 ± 2.0 mm) and controls (5.9 ± 1.5 mm, P < 0.05); however, the ratios of enlarged TV did not differ among the three groups (P = 0.059). When cutoff value was set at 6.8 mm, the TV width had a relatively high sensitivity and specificity in discriminating between PDD and PD groups (P = 0.030) and between PDD group and controls (P = 0.003), based on ROC curve analysis. In PDD patients, SN+ was more frequently detected in akinetic-rigid subgroup, and patients with SN+ showed significantly higher Hoehn and Yahr stage and Nonmotor Symptoms Questionnaire scores (P < 0.05). Conclusions: Compared to Chinese patients with PD, patients with PDD had a wider TV, altered SN sonographic features, and more severe clinical symptoms. Our findings suggest that TCS can be used to assess brain atrophy in PD and may be useful in discriminating between PD with and without dementia.